A common molecular basis for three inherited kidney stone diseases. - Lloyd, SE; Pearce, S; Fisher, S; Steinmeyer, K; Schwappach, B; Scheinman, S; Harding, B; Bolino, A; Devoto, M; Goodyer, P; Rigden, S; Wrong, O; et al. (1996)
Kidney stones (nephrolithiasis), which affect 12% of males and 5% of females in the western world, are familial in 45% of patients and are most commonly associated with hypercalciuria. Three disorders of hypercalciuric nephrolithiasis (Dent's disease, X-linked recessive nephrolithiasis (XRN), and X-linked recessive hypophosphataemic rickets (XLRH)) have been mapped to Xp11.22 (refs 5-7). A microdeletion in one Dent's disease kindred allowed the identification of a candidate gene, CLCN5 (refs 8,9) which encodes a putative renal chloride channel. Here we report the investigation of 11 kindreds with these renal tubular disorders for CLCN5 abnormalities; this identified three nonsense, four missense and two donor splice site mutations, together with one intragenic deletion and one microdeletion encompassing the entire gene. Heterologous expression of wild-type CLCN5 in Xenopus oocytes yielded outwardly rectifying chloride currents, which were either abolished or markedly reduced by the mutations. The common aetiology for Dent's disease, XRN and XLRH indicates that CLCN5 may be involved in other renal tubular disorders associated with kidney stones.